Depressive spectrum disorders in cancer: prevalence, risk factors and screening for depression: a critical review. (1st February 2017) - Caruso, R.; Nanni, M. G.; Riba, M.; Sabato, S.; Mitchell, A. J.; Croce, E.; Grassi, L.
Abstract: Background: Although depression and mood-related disorders are common in persons with cancer, these conditions remain frequently overlooked in clinical practice. Negative consequences of depressive disorder spectrum have been reported (e.g. suicidal ideation, increase physical complications and somatic symptoms, negative influence on prognosis), indicating the need for routine screening, assessment and management. Methods: A search of the major databases (Medline, Embase, PsycLIT, PsycINFO, and the Cochrane Library) was conducted on the reviews and meta-analyses available in order to summarize relevant data concerning depressive disorders spectrum in terms of prevalence, risk factors, and screening and assessment among patients with cancer across the trajectory of the disease. Results: The data show a prevalence of depression and depressive disorders between 5% and 60% according to the different diagnostic criteria, the tools used in the studies (e.g. semi-structured psychiatric interview and psychometric questionnaires), as well as the stage and type of cancer. Furthermore, despite the significant health care resources devoted to cancer care and the importance of addressing depressive symptoms, assessment and management of depressive spectrum disorders in cancer patients remains suboptimal. Conclusions: Routine screening and adequate assessment of depressive spectrum disorders is necessary in patients with cancer in order to effectively manage the multifaceted and complex consequences on cancer care.